Strategi Baznas Dalam Optimisasi Pembayaran Zakat Maal Di Daerah Mersam Kabupaten Batang Hari: Studi Kasus Pada BAZNAS Kabupaten Batang Hari - Dian Sapitri; Efni Anita; Rohana Rohana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
In this thesis the author examines research on the BAZNAS Strategy in Optimizing Zakat Maal Payments. In Kembang Paseban Village, Mersam District. This type of research is descriptive qualitative, namely describing a situation with words based on visible facts. The data used in this research uses primary data and secondary data. From the results of this research, it can be concluded that the strategy used in optimizing the payment of zakat maal, namely by using planning, organizing, implementing, monitoring, is optimal and effective, but in its implementation there are still things that need to be done. evaluated. Then the obstacles to society preferring to pay zakat directly to mustahiq rather than to amil zakat bodies are due to the lack of public understanding regarding BAZNAS, lack of public trust because BAZNAS's performance has not been seen to help the people around them, they do not know government regulations, then the location of BAZNAS is quite far from their location. stay.